Validation of HPLC–MS/MS methods for analysis of loxapine, amoxapine, 7-OH-loxapine, 8-OH-loxapine and loxapine N-oxide in human plasma. (December 2010) - Zimmer, Jennifer SD; Needham, Shane R; Christianson, Chad D; Piekarski, Crystal M; Sheaff, Chrystal N; Huie, Keith; Reed, Andrea R; Takahashi, Lori
Background: Two ESI-LC–MS/MS methods were validated for the quantitative analysis of loxapine, amoxapine, 7-OH-loxapine, 8-OH-loxapine and loxapine N -oxide in human K2 EDTA plasma. Cation-exchange solid-phase extraction (SPE) was used to extract loxapine, amoxapine and the two hydroxylated metabolites, and organic precipitation was used to quantify loxapine N -oxide.Results: Both methods were shown to be accurate (±13%), intra-assay precision was less than 15%, and inter-assay precision was less than 10% in all instances across the entire dynamic range of the assays (0.0500–50.0 ng/ml for the SPE method and 0.100–25.0 ng/ml for the precipitation method).Conclusion: The validated methods for loxapine, amoxapine, 7-OH-loxapine, 8-OH-loxapine and loxapine N -oxide have been used to successfully support clinical trials.